Rapid-prototype endoprosthesis for palliative reconstruction of an upper extremity after resection of bone metastasis - Dumnoensun Pruksakorn (2018)
© 2014, CARS. Purpose : To present a rapid-prototype (RP) endoprosthesis replacement after tumor resection in patients with bone metastasis of the upper extremity. The short-term complications and functional outcomes were evaluated as well as the survival of patients and endoprosthesis.Methods : Bone metastasis patients who required bone resection and endoprosthesis replacement were enrolled and consented before operation. Custom-made endoprosthesis was fabricated from polymethyl methacrylate assisted by RP technology. After surgery was performed, patients were followed up daily until discharge and monthly until 6 months postoperatively for immediate post-operative complications and for signs of endoprosthesis failure. The functional outcome was evaluated 6 months postoperatively by the Musculoskeletal Tumor Society score (MTSS) and the Mankin score. Thereafter, patients’ survival and arm condition were monitored every 3 months.Results : Sixteen cases participated on this study. There were nine proximal-, four total- and two distal humerus, and one proximal ulna replacement. The median follow-up period was 486 days. The mean MTSS was 55 % and the Mankin score was good in 64 % and fair in 36 % of the patients. Glenohumeral subluxation was observed in 23 % of the patients; however, a stable shoulder was achieved in all cases. There were no prosthesis failure or systemic breakage.Conclusions : An RP endoprosthesis may have significant advantages when the entire humerus needs to be replaced, or periarticular sites are involved. This technique offers custom-made endoprosthesis with enough durability, and in a relatively short production time at reasonable costs which are suitable for palliative reconstruction.